Sistem Informasi Penjualan Berbasis Web Di PT Hanbro Tekno Utama - Rangga Rakhazona Pamungkas (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
PT HANBRO TEKNO UTAMA is a startup company engaged in the field of Electrical and Mechanical Engineering Consultants. However, the recording of sales data information at PT HANBRO TEKNO UTAMA only uses numeric data processing software that does not yet have a centralized database and the Sales Information System is not well structured. This hampers business development at PT HANBRO TEKNO UTAMA. With this Web-Based Information System, so that it can be a solution in business development. This Web-Based Information System was created with the PHP programming language, Javascript, MySql database, and CodeIgniter framework.